Mechanistic inhibition of Monkeypox and Marburg virus infection by O-rhamnosides and Kaempferol-o-rhamnosides derivatives: a new-fangled computational approach - Al Mashud, Md. Abdullah; Kumer, Ajoy; Mukerjee, Nobendu; Chandro, Akhel; Maitra, Swastika; Chakma, Unesco; Dey, Abhijit; Akash, Shopnil; Alexiou, Athanasiosis; Khan, Azmat Ali; Alanazi, Amer M.; Ghosh, Arabinda; et al. (Frontiers in Cellular and Infection Microbiology, 2023)
The Monkeypox virus (Mpox) and the Marburg virus (MARV) have been considered more common and infecting people worldwide. This has made a lot of severity for world leaders because the effects could be found deadly disease. Only a few treatments, therapy, or vaccines can be used to treat Mpox or MARV infections right now. However, in this study, several O-rhamnosides and Kaempferol-O-rhamnosides were put through a succession of molecular modeling methods, such as ADMET, molecular docking, and molecular dynamics/MD simulation. Both of these compounds can act as inhibitors of the Mpox and MARV. The accuracy of the Prediction of Activity Spectra for Substances (PASS) prediction was checked to see if they were effective against viruses. The most important part of this study is molecular docking prediction. It has been found that ligands (L07, L08, and L09) bind to Mpox (PDB ID: 4QWO) and MARV (PDB ID: 4OR8) with binding affinities show range from -8.00 kcal/mol to -9.5 kcal/mol. The HOMO-LUMO-based quantum calculations are used to find the HOMO-LUMO gap of frontier molecular orbitals (FMOs) and these values are also used to estimate the chemical potential, electro negativity, hardness, and softness. Drug similarity and AD-MET prediction assessments of pharmacokinetic phenomena also showed that the compounds were probably not cancer-causing or harmful for the liver, and dissolved quickly. Ultimately, molecular dynamic (MD) modeling determined which bioactive chemicals had the best-docked complexes. MD simulations show that different kinds of kaempferol-O-rhamnoside are needed to ensure that the docking validation works and that docked complex stays stable. Also, these results could make it easi-er to find new chemicals that could be used to treat illnesses caused by the Monkeypox virus and the Marburg virus.